A STUDY ON QUALITATIVE RESEARCH TO THE DEVELOPMENT OF ENGLISH LANGUAGE TEACHING (ELT) IN INDONESIA - Udi Samanhudi; Silvia Widianingsih (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2017)
English language teaching (ELT) in Indonesiahas long benefited from qualitative research in terms of problems explorations as well as efforts aim to develop the practice of teaching and learning of Englishwriting conducted byscholars working under the field.Focusing on the analysis of qualitative research contributions to the practice of English writing pedagogy research in Indonesia, the results suggest that this research approachis suitable to apply in ELT practice in the country as it provides a better description of real problems occurring in the site in dealing with writing English practices as well as prompt solutions of those problems. In short, as results of the analysis revealed, qualitative research is not only a potential research approach to solve educational problems such as in the case of ELT in Indonesia but also clearly is an evident of a research approach that helps to improve this field.